Impact of corporate social responsibility on automotive firm performance - Lin, Woon Leong (2019)
Prevailing studies on the economic implications of corporate social responsibility (CSR) for companies have, for the most part, emphasised the positive facets of CSR, failing to see that firms also espouse behaviours and initiatives which can be termed as negative CSR. In view of this, this study presents a framework connecting positive as well as negative CSR to firm performance. Acknowledging societal needs and having effective dialogue with shareholders and stakeholders regarding firms' social profiles as well as risk management practices are likely to reduce the firm risk, shape firms' reputation and enhance profitability. These are indeed valuable in the wake of the scandals for car maker’s continuity and enhancing shareholder value. It is argued that effective competitive action and innovation are likely to encourage more CSR activities, reputation and risk management, which in turn is expected to improve stock prices, profits, enhance firm value and reduce return volatility. This study examines the potential relationship between CSR (Positive CSR and Negative CSR), firm performance, firm risk levels, and corporate reputation. It contributes toward a better understanding of the influence of internal competitive action and innovation mechanisms on positive and negative CSR and their substantive consequences on firm performance. Examining 132 top automotive firms, this study uses the dynamic panel data system Generalise Moment of Method (GMM) estimates to analyse the relationship between positive CSR, negative CSR and firm performance (e.g., corporate financial performance (CFP), firm risk and corporate reputation); this study also examined the moderating role of competitive action and innovation on the CSRFP relationship. Based on an investigation of secondary information of 132 global automotive firms, over the period of 2011–2017, this study found evidence supporting the relationship between positive CSR and negative CSR and firm performance and showed that CSR significantly impacted firm performance, with positive CSR improving it and negative CSR harming it. Correspondingly, the outcomes indicated that there was no guarantee of the augmentation in firm performance from positive CSR, with firms possessing high degrees of competitive action and innovation experiencing higher firm performance. The results also suggested that higher positive CSR score reduced uncertainties of firm risk, improved firm’s profitability and provided investors with valuable information to assess financial assets and monitor management practices. This was reflected as an improvement to Goodwill, Return On Assets and Return On Equity and reduction to return volatility when the present of competitive action and innovation.